Is DBM Beneficial for the Enhancement of Bony Consolidation in Distraction Osteogenesis? A Randomized Controlled Trial. (29th January 2015) - Song, Sang-Heon; Kim, Sang-Gyun; Kim, Sung-Eun; Song, Hae-Ryong
Abstract : The aim of the present study was to compare the radiographic and clinical outcomes of DBM injection and conventional treatment during tibial lengthening over an intramedullary nail in adult patients with short stature. Twenty-nine patients were randomized to receive DBM injection (n = 14 ) or conventional treatment without any injection (n = 15 ) and evaluated. The outcome was measured on the basis of the pixel value ratio (PVR) in the digital radiographs during the consolidation period; healing index; clinical assessment; and the rate of complications. In the DBM group, the mean PVR of 1 (mineral density of the callus is comparable to the adjacent bone) was reached by 40 weeks in anterior and medial cortices which was significantly different than that in the control group (P = 0.03 for anterior cortex; P = 0.04 for medial cortex). The average healing index in the DBM group was 39.8 ± 5.3 days/cm compared to 44.3 ± 5.8 days/cm in the control group (P = 0.05 ). There were no significant differences in clinical outcomes (P = 0.23 ) and functional status (P = 0.47 ) including complications (P = 0.72 ) between two groups. In this randomized clinical trial, injection of DBM at the time of initial operation enhanced consolidation of regenerate callus without interfering with clinical outcomes compared to that with conventional treatment.